PENGARUH MODEL PEMBELAJARAN INQUIRY TRAINING TERHADAP HASIL BELAJAR SISWA KELAS X DI SMA NEGERI 3 BORONG - Yovita Angol Vigo; Melkyanus Bili Umbu Kaleka; Yasinta Embu Ika (ScienceEdu, 2023)
This study aims to determine the effect of the learning model. Inquiry Training on Learning Outcomes of Class X Students at SMA Negeri 3 Borong. The type of research used was quantitative by design, quarry experiment with a posttest-only control group design. The population in this study were all class X students at SMA Negeri 3 Borong totaling 58 people. The sample of this study consisted of 2 classes obtained using a random sampling technique, namely class X-A as many as 29 people as an experimental class using the inquiry learning model and class X-B as many as 29 people as a control class using conventional learning. tests in the form of multiple choice tests, tests to measure student learning outcomes, data analysis using uit. The results of the study using SPSS 28 obtained the results of the analysis, namely a significant value for (ig 2-tailed) of 0.001 0.05, which means that there is an effect of applying the inquiry training learning model on student learning outcomes.